BMI-stratified phenotypes of polycystic ovary syndrome: advances in gut microbiota research and personalized management strategies - Su, Bisha; Cao, Yining; Ma, Lin; Huang, Jian (Frontiers in Endocrinology, 2026)
Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine-metabolic disorder affecting 11%-13% of women of reproductive age. Based on body mass index (BMI), patients can be phenotypically classified into obese and non-obese subgroups: the obese PCOS is characterized by insulin resistance, hyperandrogenemia, and metabolic syndrome, with more pronounced metabolic risks; non-obese PCOS primarily manifests as reproductive endocrine dysfunction. In recent years, studies have shown that the Gut microbiota plays a key role in the pathogenesis of PCOS, and dysbiosis in the obese subgroup is generally more pronounced, potentially amplifying metabolic abnormalities through pathways such as short-chain fatty acids, bile acid disturbances, and endotoxin-related low-grade inflammation. This review systematically summarizes the clinically heterogeneous features of BMI-stratified PCOS and its gut microbiota characteristics, with a focus on elucidating the mechanistic differences between obese and non-obese individuals in terms of inflammation, metabolites, and endocrine regulatory pathways. Based on current evidence, individualized intervention strategies targeting different BMI subtypes are proposed, including dietary and lifestyle modifications, interventions with probiotics/prebiotics/synbiotics, and exploration of emerging precision microbiome therapies such as fecal microbiota transplantation. The interaction between BMI and gut microbiota provides new directions for stratified management and personalized treatment of PCOS; however, high-quality longitudinal and interventional studies are still needed to clarify causal relationships and optimize microbiota-targeted strategies.